ANALISIS YURIDIS AKIBAT HUKUM MUSNAHNYA OBJEK JAMINAN FIDUSIA DALAM PERJANJIAN PEMBIAYAAN KONSUMEN (STUDI DI PT.WOM FINANCE, Tbk ) - ANITA SERVIA NABABAN (jurnal.unprimdn.ac.id, 2021)
PT. WOM Finance, Tbk. is one of the companies operating in motorcycle financing. PT. WOM Finance, Tbk. cannot be separated from debtor’s/consumer’s default or the disappearance of motorcycles/security object. It copes with the risk by making a financing agreement consisting of primary agreement and the other supporting agreement such as loan agreement, fiduciary agreement, power of attorney and insurance. The objective of this research is to discover the mechanism of consumer finance, debtor’s liability for default, and legal protection for creditor in case of disappearance of fiduciary security object in which the debtor has defaulted earlier.This is an analytical prescriptive research with normative juridical method. It is conducted by studying references or secondary data including legal norms in the prevailing laws and regulation or documents related to the juridical consequences i.e. disappearance of security object in consumer finance agreement in PT. WOM Finance, Tbk. in order to answer the research problems.The results of the research discover the finance mechanism in PT.WOM Finance, Tbk. in general, the financing starts from an application and ends with the execution of the agreement. The defaults performed by a debtor causes legal consequences for the debtor themselves. In case the fiduciary security object disappears when the debtor has defaulted earlier, the creditor does not only obtain legal protection from the Consumer Finance Agreement, but it also gains the protection from Insurance Agreement.